Teknologi Pembuatan Silase di Dusun Kampung Baru, Desa Sidosari, Natar, Lampung Selatan - Nani Irwani; Dwi Desmiyeni Putri; Dina Tri Marya; Intan Kamilia Habsari; Gusma Gama Maradon; Neko Riffiandi (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
The purpose of community service activities for silage-making technology is to learn about maintenance management and animal feed technology to increase cattle productivity in Sidosari Village, Natar District, South Lampung. The methods of activities carried out in this service are monologue, grant, and practice. The technology transfer activity for making silage to cattle farmers in the Sidosari Village, Natar District, South Lampung, provides knowledge and transfers technology to them in processing animal feed with fermentation technology. From the transfer of animal feed processing technology carried out to cattle farmers in Sidosari Natar Village, they have been able to apply silage, and this activity is the answer to the feed problems they have been facing.